Asymptotically flat Einstein-Maxwell fields are inheriting - Chrusciel, PT; Nguyen, L; Tod, P; Vasy, A (International Press, 2021)
We prove that Maxwell fields of asymptotically flat solutions of the Einstein–Maxwell equations inherit the stationarity of the metric.